New primitives of controlled elements F2/4 for block ciphers - Minh Nguyen Hieu; Duy Ho Ngoc; Canh Hoang Ngoc; Trung Dinh Phuong; Manh Tran Cong (Institute of Advanced Engineering and Science, 2020)
This paper develops the cipher design approach based on the use of data-dependent operations (DDOs). A new class of DDO based on the advanced controlled elements (CEs) is introduced, which is proven well suited to hardware implementations for FPGA devices. To increase the hardware implementation efficiency of block ciphers, while using contemporary FPGA devices there is proposed an approach to synthesis of fast block ciphers, which uses the substitution-permutation network constructed on the basis of the controlled elements F2/4 implementing the 2 x 2 substitutions under control of the four-bit vector. There are proposed criteria for selecting elements F2/4 and results on investigating their main cryptographic properties. It is designed a new fast 128-bit block cipher MM-128 that uses the elements F2/4 as elementary building block. The cipher possesses higher performance and requires less hardware resources for its implementation on the bases of FPGA devices than the known block ciphers. There are presented result on differential analysis of the cipher MM-128